Cost Utility of Supporting Family-Based Care to Prevent HIV and Deaths among Orphaned and Separated Children in East Africa: A Markov Model–Based Simulation. Issue 2 (December 2022) - Wilson-Barthes, Marta; Braitstein, Paula; DeLong, Allison; Ayuku, David; Atwoli, Lukoye; Sang, Edwin; Galárraga, Omar
Purpose. Strengthening family-based care is a key policy response to the more than 15 million orphaned and separated children who have lost 1 or both parents in sub-Saharan Africa. This analysis estimated the cost-effectiveness of family-based care environments for preventing HIV and death in this population.Design. We developed a time-homogeneous Markov model to simulate the incremental cost per disability-adjusted life year (DALY) averted by supporting family-based environments caring for orphaned and separated children in western Kenya. Model parameters were based on data from the longitudinal OSCAR's Health and Well-Being Project and published literature. We used a societal perspective, annual cycle length, and 3% discount rate. Incremental cost-effectiveness ratios were simulated over 5- to 15-y horizons, comparing family-based settings to street-based "self-care." Parameter uncertainty was addressed via deterministic and probabilistic sensitivity analyses.Results. Under base-case assumptions, family-based environments prevented 422 HIV infections and 298 deaths in a simulated cohort of 1, 000 individuals over 10 y. Compared with street-based self-care, family-based care had an incremental cost of 2, 528 per DALY averted (95% confidence interval [CI]: 1, 798, 2, 599) and 2, 355 per quality-adjusted life year gained (95% CI: 1, 667, 2, 413). The probability of family-based care being highly cost-effective was >80% at a willingness-to-pay (WTP) threshold of 2, 250/DALY averted. Households receiving government cash transfers had minimally higher cost-effectiveness ratios than households without cash transfers but were still cost-effective at a WTP threshold of twice Kenya's GDP per capita.Conclusions. Compared with the status quo of street-based self-care, family-based environments offer a cost-effective approach for preventing HIV and death among orphaned children in lower-middle income countries. Decision makers should consider increasing resources to these environments in tandem with social protection programs. Highlights: UNICEF and more than 200 other international organizations endorsed efforts to redirect services toward family-based care as part of the 2019 UN Resolution on the Rights of the Child; yet this study is one of the first to quantify the cost-effectiveness of family-based care environments serving some of the world's most vulnerable children. This health economic modeling analysis found that family-based environments would prevent 422 HIV infections and 298 deaths in a cohort of 1, 000 orphaned and separated children over a 10-y time horizon. Compared with street-based "self-care, " family-based care resulted in an incremental cost of 2, 528 per DALY averted (95% CI: 1, 798, 2, 599) and 2, 355 per quality-adjusted life year gained (95% CI: 1, 667, 2, 413) after 10 y. Annual per-child expenditures for children living in family-based care environments in sub-Saharan Africa could potentially be increased by at least 25% and remain highly cost-effective.